Spatiotemporal Control of Electrochemiluminescence Guided by a Visible Light Stimulus - Vogel, Yan; Darwish, Nadim; Ciampi, Simone (ELSEVIER, 2020)
Chemiluminescence and fluorescence have revolutionized the study of chemical and biological processes. However, unlike fluorescence, spatiotemporal control of chemiluminescence is challenging, and the technically simple solution of converting chemical energy into light energy only at specific sites defined by a clean, easy-to-deliver focused light stimulus is not yet a viable option. Here, we demonstrate the spatial and temporal control of a chemiluminescent reaction by photoinduced oxidative hotspots on a silicon surface. The excitation light is not required to pass through the liquid sample; hence, the light stimulus can excite a luminescent dye under effectively dark conditions. This provides a strategy for removing light-induced sample damages, photobleaching, and autofluorescence.